Gene Regulatory Networks Governing Lung Specification. Issue 8 (August 2014) - Rankin, Scott A.; Zorn, Aaron M.
ABSTRACT The epithelial lining of the respiratory system originates from a small group of progenitor cells in the ventral foregut endoderm of the early embryo. Research in the last decade has revealed a number of paracrine signaling pathways that are critical for the development of these respiratory progenitors. In the post‐genomic era the challenge now is to figure out at the genome wide level how these different signaling pathways and their downstream transcription factors interact in a complex "gene regulatory network" (GRN) to orchestrate early lung development. In this prospective, we review our growing understanding of the GRN governing lung specification. We discuss key gaps in our knowledge and describe emerging opportunities that will soon provide an unprecedented understanding of lung development and accelerate our ability to apply this knowledge to regenerative medicine. J. Cell. Biochem. 115: 1343–1350, 2014. © 2014 Wiley Periodicals, Inc.